Glutamate Transporter Inhibitors with Photo‐Controlled Activity. Issue 2 (16th May 2018) - Hoorens, Mark W. H.; Fu, Haigen; Duurkens, Ria H.; Trinco, Gianluca; Arkhipova, Valentina; Feringa, Ben L.; Poelarends, Gerrit J.; Slotboom, Dirk J.; Szymanski, Wiktor
Abstract : Glutamate is an important signaling molecule in the nervous system and its extracellular levels are regulated by amino acid transporters. Studies on the role of glutamate transport have benefitted from the development of small molecule inhibitors. Most inhibitors, however, cannot be remotely controlled with respect to the time and place of their action, which limits their application in biological studies. Herein, the development and evaluation of inhibitors of the prokaryotic transporter GltTk with photo‐controlled activity, enabling the remote, reversible, and spatiotemporally resolved regulation of transport is reported. Based on a known inhibitor, seven inhibitors, bearing a photoswitchable azobenzene moiety, are designed and synthesized. The most promising photo‐controlled inhibitor, shows in its non‐irradiated form, an IC50 of 2.5 ± 0.4 μm for transport by GltTk . Photoswitching results in a reversible drop of potency to an IC50 of 9.1 ± 1.5 μm . This 3.6‐fold difference in activity is used to demonstrate that the transporter function can be switched on and off reversibly through irradiation. As a result, this inhibitor could be a powerful tool in studying the role of glutamate transport by precisely controlling the time, and the specific tissue or groups of cells, in which the inhibitor is active. Abstract : The design, synthesis and evaluation of the photochemical and biological properties of light‐controlled glutamate transporter inhibitors is presented . Application of these compounds enables remote, reversible and spatiotemporally resolved regulation of activity of an important class of transporter proteins.